Synthesis of (E)‐3‐(2‐Oxo‐2‐arylethylidene)indolin‐2‐ones through Alkyne Carbonyl Metathesis and Their Stereospecific Application towards Spiro‐oxindolopyrrolizidine Scaffolds. Issue 12 (30th March 2018) - Basu, Soumyadip; Mukhopadhyay, Chhanda
Abstract : An iron‐salt catalyzed, atom economic, unfamiliar type of alkyne carbonyl metathesis strategy has been developed by using isatins and acetylenes for the regioselective synthesis of ( E )‐3‐(2‐oxo‐2‐arylethylidene)indolin‐2‐one derivatives, which has been further utilized to develop a catalyst‐free methodology for the synthesis of biologically active spiro‐oxindolopyrrolizidine scaffolds in a highly regio‐ and stereospecific manner by reacting withl ‐proline and aldehydes. Both methods are acceptable towards various functionalities that include electron‐donating and electron‐accepting groups at the ortho ‐, meta ‐ and para ‐positions. This protocol provides an environmentally friendly reaction methodology for the synthesis of a series of (1′ S, 2′ R, 3′ R, 7a′ R )‐1′, 3′, 5′, 6′, 7′, 7a′‐hexahydrospiro[indoline‐3, 2′‐pyrrolizin]‐2‐ones. Abstract : A transition metal salt catalyzed alkyne carbonyl metathesis followed by a multicomponent protocol to synthesize highly substituted new (1′ S, 2′ R, 3′ R, 7a′ R )‐1′, 3′, 5′, 6′, 7′, 7a′‐hexahydrospiro[indoline‐3, 2′‐pyrrolizin]‐2‐ones. A total of 39 compounds were synthesized by an interesting combination of metal‐salt catalysis and a multicomponent strategy.